Interpretation of elevated high-sensitivity cardiac troponin I in elite soccer players previously infected by severe acute respiratory syndrome coronavirus - Mascia, G.; Pescetelli, F.; Baldari, A.; Gatto, P.; Seitun, S.; Sartori, P.; Pieroni, M.; Calò, L.; Della Bona, R.; Porto, I. (International Journal of Cardiology, 2020)
Objectives: To clarify the meaning of elevated cardiac troponin in elite football athletes previously infected with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and screened for cardiovascular involvement in the wake of competitive sport resumption. Methods: We designed a retrospective cohort study with the collaboration of two Italian Serie A teams. Football players from both rosters (58 athletes) were systematically analysed. For every SARS-CoV-2 positive athlete, the Italian Football Federation protocol requested full blood tests including high-sensitivity cardiac troponin I (hscTnI), along with a complete cardiovascular examination. We extended the analysis to SARS-CoV-2 negative athletes. Results: A total of 13/58 players (22.4%) suffered from SARS-CoV-2infection: all had a negative cardiovascular examination and 2/13 (15%) showed increased hs-cTnI values (120,8 pg/ml and 72,6 pg/ml, respectively; upper reference level 39,2 pg/ml), which did not track with inflammatory biomarkers. Regarding the 45/58 (77,6%) non infected athletes, a slight increase in hs-cTnI was observed in 2 (4.5%) subjects (values: 61 pg/ml and 75pg/ml respectively). All hs-cTnI positive athletes (4/58, 7%) underwent cardiac magnetic resonance (CMR), that excluded any cardiac injury. Conclusions: In our retrospective study, SARS-CoV-2 infection in elite football athletes was not associated to clinical or biomarkers abnormalities. Increased hs-cTnI was rare and not significantly associated with previous SARS-COV2 infection nor with pathological findings at CMR, albeit elevated hs-cTnI was numerically more prevalent in the infected group.